Answer:
Option C) [tex]a_{n}=m-b+m(n-1)[/tex] for [tex]n={\{1,2,3,...}\}[/tex] is not the correct way to define the given infinite sequence
[tex]{\{m+b,2m+b,3m+b,4m+b,...}\}[/tex]
Step-by-step explanation:
Given infinite sequence is [tex]{\{m+b,2m+b,3m+b,4m+b,...}\}[/tex]
Option B) [tex]a_{n}=m-b+m(n-1)[/tex] for [tex]n={\{1,2,3,...}\}[/tex] is not the correct way to define the given infinite sequence [tex]{\{m+b,2m+b,3m+b,4m+b,...}\}[/tex]
Now verify [tex]a_{n}=m-b+m(n-1)[/tex] for [tex]n={\{1,2,3,...}\}[/tex] is true for the given infinite sequence
That is put n=1,2,3,.. in the above function
[tex]a_{n}=m-b+m(n-1)[/tex]
When n=1, [tex]a_{1}=m-b+m(1-1)[/tex]
[tex]=m-b+0[/tex]
[tex]a_{1}=m-b\neq m+b[/tex]
When n=2, [tex]a_{2}=m-b+m(2-1)[/tex]
[tex]=m-b+m[/tex]
[tex]a_{2}=2m-b\neq 2m+b[/tex]
When n=3, [tex]a_{3}=m-b+m(3-1)[/tex]
[tex]=m-b+2m[/tex]
[tex]a_{3}=3m-b\neq 3m+b[/tex]
and so on.
Therfore [tex]a_{n}=m-b+m(n-1)[/tex] for [tex]n={\{1,2,3,...}\}[/tex] is not the correct way to define the given infinite sequence
[tex]{\{m+b,2m+b,3m+b,4m+b,...}\}[/tex]
Therefore option C) is correct